Предмет: Алгебра,
автор: l38890519
2) x + 12 _ x-1 _ x+1. 9 6 3
Приложения:
Ответы
Автор ответа:
1
Ответ:
(Х + 12) / 9 - (Х - 1) / 6 = (Х + 1) / 3
Объяснение:
если нужно решение, то вот
2 (Х + 12) - 3 (Х - 1) = 6 (Х + 1)
2 х + 24 - 3 х + 3 = 6 х + 6
- Х + 27 = 6 х + 6
7 х = 21
Х = 3
l38890519:
спасибі
Похожие вопросы
Предмет: Литература,
автор: anneto4kar
Предмет: Математика,
автор: sopotnasta
Предмет: История,
автор: olesamorozova535
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: deniza19082008